2016
DOI: 10.5194/isprs-archives-xli-b2-695-2016
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Influence of Tree Coverage on Property Crime: A Case Study in the City of Vancouver, British Columbia, Canada

Abstract: ABSTRACT:With the development of Geographic Information Systems (GIS), crime mapping becomes an effective approach to investigate the spatial pattern of crime in a defined area. Understanding the relationship between crime and its surrounding environment can reveal possible strategies that can reduce crime in a neighbourhood. The relationship between vegetation density and crime has been under debate for a long time. This research is conducted to investigate the impacts of tree coverage on property crime in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Indeed, the evidence is far more consistent when examining violent crime, rather than property crime, as the outcome (see Bogar & Beyer, 2015). Some studies have found a negative association between greenspace and property crime (Chen et al., 2016; Ogletree et al., 2022); however, others have found either no association or a positive association (Hipp et al., 2022a; Schusler et al., 2018; Wolfe & Mennis, 2012). Across precincts in South Africa, for instance, tree canopy was associated with lower violent crime rates but with higher property crime rates (Venter et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the evidence is far more consistent when examining violent crime, rather than property crime, as the outcome (see Bogar & Beyer, 2015). Some studies have found a negative association between greenspace and property crime (Chen et al., 2016; Ogletree et al., 2022); however, others have found either no association or a positive association (Hipp et al., 2022a; Schusler et al., 2018; Wolfe & Mennis, 2012). Across precincts in South Africa, for instance, tree canopy was associated with lower violent crime rates but with higher property crime rates (Venter et al., 2022).…”
Section: Introductionmentioning
confidence: 99%